Role of p-ERK1/2 in Benign Prostatic Hyperplasia during Hyperinsulinemia - Li, Yong-Zhi; Shi, Ben-Kang; Li, Jing-Yu; Zhu, Xing-Wang; Liu, Jia; Liu, Yi-Li (Urology Journal, 2020)
Purpose: Using a rat model of hyperinsulinemia, the present study investigated the role of p-ERK1/2 in benign prostatic hyperplasia (BPH). Materials and Methods: Forty male Sprague-Dawley rats were randomly selected and assigned to four groups: high fat diet (HFD)+BPH (n=10), HFD (n=10), BPH (n=10), and control (n=10) groups. Hyperinsulinemia was induced by HFD feeding, while BPH was induced using testosterone propionate. Plasma glucose, plasma insulin and bodyweight were examined weekly. Immunohistochemistry (IHC) and western blot analysis were used to analyze the expression of ERK1/2 and p-ERK1/2 in rat prostates. Results: Plasma glucose and plasma insulin levels were significantly greater in the HFD+BPH and HFD groups, when compared to the other two groups (P<0.05). Prostate weights were significantly greater in the HFD+BPH, HFD and BPH groups, than in the control group (P<0.05). IHC and western blot analysis revealed that p-ERK1/2 expression was greater in the HFD+BPH group than in the other three groups (P<0.05). Conclusion: Androgens plus a hyperinsulinemic condition induced by HFD can result in prostatic cell hyperplasia, and this mechanism may be correlated to the upregulation of p-ERK1/2. Further investigations of this possibility are required.